Modern advances in intelligent systems and tools - Ding, Wei (Studies in Computational Intelligence, 2012)
Intelligent systems provide a platform to connect the research in artificial intelligence to real-world problem solving applications. Various intelligent systems have been developed to face real-world applications. This book discusses the modern advances in intelligent systems and the tools in applied artificial intelligence. It consists of twenty-three chapters authored by participants of the 25th International Conference on Industrial, Engineering & Other Applications of Applied Intelligent Systems (IEA/AIE 2012) which was held in Dalian, China. This book is divided into six parts, including Applied Intelligence, Cognitive Computing and Affective Computing, Data Mining and Intelligent Systems, Decision Support Systems, Machine Learning, and Natural Language Processing. Each part includes three to five chapters. In these chapters, many approaches, applications, restrictions, and discussions are presented. The material of each chapter is self-contained and was reviewed by at least two anonymous referees to assure the high quality. Readers can select any individual chapter based on their research interests without the need of reading other chapters. We hope that this book provides useful reference values to researchers and students in the field of applied intelligence. We also hope that readers will find opportunities and recognize challenges through the papers presented in this book.